The Role of the Media in Empowering People with Disabilities to Participate in Society (Journal Of Educational and Psychological Researches, 2022)
Disabled people are among the most important groups that need attention, care, and financial and moral care. They cannot fulfill the requirement of life normally without care from a person to meet their special needs. The disability is either mental or physical. The Iraqi government has paid attention to this category by adopting a law for this category, represented by Law No. (38) for the year (2013), which keeps their rights and duties in Iraqi society by  establishing institution of persons with disabilities and special needs of the Ministry of Labor and Social Affairs to create a modern society politically, socially, culturally or economically. In view of the importance of this group in society, the media reinforces the community awareness to integrate and empower them to serve society, as well as their equality with their peers in society and their enjoyment of their various human rights on the one hand and raise the spirits and confidence of this group in its capabilities in Iraqi society. The research includes three main topics. The first topic is the methodological framework (the problem of research, its objectives, its importance, the research community, and the method used in it and the validity of the analysis). The second topic deals with (the role of the media in enabling disabled people to participate in Iraqi society). The third topic represents (field study on a sample of people with disabilities to reach the desired goal of the research).